Workplace Inclusion in Academia: The Relationship between Diversity Climate and Engineering Faculty Turnover Intentions - Henry Tran; Spencer Platt; Ruiqin Gao; Jungsun Go (SAGE Publishing, 2024)
The purpose of this study is to examine the relationship between engineering faculties' perception of the diversity climate and their turnover intentions at R1 (Research 1) universities across the U.S. We sampled 1,101 tenure-track engineering faculty for this purpose. Data analysis showed that an engineering faculty's demographic characteristics (i.e., sex, race/ethnicity, professor rank, age, engineering areas, marriage status, and tenure-track status) are associated with their perceptions of the diversity climate. Furthermore, results from structural equation modeling analyses show that faculty with higher perceptions of organizational fairness and inclusion reported a lower desire to turn over. Implications for the results are discussed.